(untitled) (Altre Modernità, 2016)
The essay proposes, from a descriptive and intercultural view, the approach to both (para)textual and textual information around television series, involving gender(ed) features, attitudes, and values. Those texts are being translated, released and spread all over the world and, therefore, contribute to the global stereotyping of a (supposed to be) new American woman. Under the patronage of Descriptive Translation Studies and going beyond, a thick approach to the act of translating is proposed, in order to map entirely the translated product. With a balanced combination, which puts together a linguistic microscope and a cultural telescope, a catalogue (and subsequent corpus of data) will be portrayed, allowing the analysis of the rewritten texts broadly. The inventory is made up of a number of TV series getting a good mark for the Bechdel test, which (seemingly) challenge old stereotypes in order to build up a new image of woman. Placing considerable importance on ideology in Translation Studies and, by doing so, refusing and turning down the view of the translation as a neutral bridge, an invisible agent, we will pay attention to the fact that not only linguistic but especially cultural, and even ideological, differences arouse when dealing with the act of translating. In particular, we will focus on the subject of manipulation and rewriting of stereotypes in the field of audiovisual translation.